Beyond RF ablation other uses for RF within the body - Murphy,O; Bahmanyar,MR; McLeod,CN; Toumazou,C; Yacoub,M (2016)
The use of high frequencies within the body is commonplace for treatment and imaging, but, other than a few examples very little exists in terms of RF sensors and for communication deep into the body. This paper will give an overview of an RF powered implantable blood pressure sensor for continuous monitoring and in doing so demonstrate the use of RF within the body.